Respuesta :

[tex]\tan(a+b)=\dfrac{\tan a+\tan b}{1-\tan a\tan b}[/tex]
[tex]\implies\tan(\sin^{-1}x+\cos^{-1}y)=\dfrac{\tan(\sin^{-1}x)+\tan(\cos^{-1}y)}{1-\tan(\sin^{-1}x)\tan(\cos^{-1}y)}[/tex]

If [tex]\theta=\sin^{-1}x\implies\sin\theta=x[/tex], then

[tex]\tan(\sin^{-1}x)=\tan\theta=\dfrac{\sin\theta}{\cos\theta}[/tex]

and we know from the Pythagorean identity that [tex]\cos\theta=\sqrt{1-\sin^2\theta}[/tex], so that

[tex]\tan(\sin^{-1}x)=\dfrac x{\sqrt{1-x^2}}[/tex]

Similarly, if we let [tex]\varphi=\cos^{-1}y\implies\cos\varphi=y[/tex], we have

[tex]\tan(\cos^{-1}y)=\tan\varphi=\dfrac{\sin\varphi}{\cos\varphi}=\dfrac{\sqrt{1-y^2}}y[/tex]

So,

[tex]\tan(\sin^{-1}x+\cos^{-1}y)=\dfrac{\frac x{\sqrt{1-x^2}}+\frac{\sqrt{1-y^2}}y}{1-\frac{x\sqrt{1-y^2}}{y\sqrt{1-x^2}}}[/tex]
[tex]\tan(\sin^{-1}x+\cos^{-1}y)=\dfrac{xy+\sqrt{1-x^2}\sqrt{1-y^2}}{y\sqrt{1-x^2}-x\sqrt{1-y^2}}[/tex]
ACCESS MORE